IDENTIFYING THE IMPORTANCE OF GRAMMATICAL NORMS IN RAPID ENGLISH LANGUAGE LEARNING - Shohrasul Namozov (Bright Mind Publishing, 2025)
The importance of grammatical norms in accelerated English language learning lies in their capacity to provide a clear, structured foundation for communication. In the context of Uzbekistan’s secondary education system, particularly in grades 9 to 11, the role of grammar becomes vital as students prepare for academic and professional environments that demand proficiency in English. This paper explores the value of grammatical instruction in the fast-paced teaching of English, emphasizing how grammatical awareness contributes to accurate and fluent expression. It draws attention to how targeted grammar instruction enhances students’ confidence, reduces communication errors, and accelerates the language acquisition process. By focusing on practical classroom strategies and empirical evidence from English teaching in Uzbek schools, the study highlights the need for an integrated approach where grammar is not taught in isolation but in meaningful contexts. Ultimately, this research aims to support educators in optimizing teaching methodologies that balance communicative fluency with grammatical precision, leading to more efficient and sustainable language learning outcomes for high school students in Uzbekistan.
Keywords: Grammatical norms, English language teaching, accelerated learning, secondary education, communicative competence, language acquisition.